Explanatory Sequential Review of The Influence of Recitation and Motivation Methods on Student Learning Achievement - Feren Fedora; Muh. Asharif Suleman; Kurnia Sandi; Zulfi Idayanti; Shaleh Shaleh (International Journal of Science and Applied Science: Conference Series, 2024)
Abstract: This study aims to determine the influence of recitation method and motivation on the achievement of learning This study used quantitative methods with three variables, namely the recitation method (X1), Motivation (X2) and Learning Achievement (Y), the number of populations in this study was 180, then the researcher found 50 sempel taken using the Stratifed random sempilng formula. Data collection using questionnaire and documentation methods. Analysis of the instrument includes validity tests and reliability tests with Cronbach's. The analysis uses multiple linear regression analysis. Based on the analysis process, the magnitude of the influence of the recitation method and motivation on natural science learning achievement is shown from the magnitude ofthe coefficient of determination (R Square) value of 61.4% while the remaining 38.6% of natural science learning achievement is influenced by other factors that are not explained in this study. The results found that there was a significant influence of recitation methods and motivation on student achievement in natural science subjects. This means that the recitation method accompanied by motivationwill make students more active in learning.